2002
DOI: 10.1590/s1415-43662002000200013
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas do albedo em três ecossistemas da floresta amazônica

Abstract: Os albedos relativos às radiações de ondas curtas, infravermelho e fotossinteticamente ativa foram estimados para três ecossistemas da floresta amazônica. A pesquisa foi conduzida nas áreas de Campina e Campinarana, na Reserva Biológica de Campina, localizada no quilômetro 46 da rodovia BR-174 (2º 34'S; 60º 02'W), que liga Manaus a Caracaraí e na área de Mata Densa, na Reserva Florestal Ducke (2º 57'S; 59º 57'W). Para obtenção dos dados nos diferentes tipos de vegetação, foi instalado, numa torre metálica, um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
(4 reference statements)
0
4
1
9
Order By: Relevance
“…Table I shows the basic statistics of the daily data, including the maximum and minimum values found at each height. These variations during the day refer exclusively to the relationship between reflection and solar declination, as reported by Leitão et al (2002). The highest standard deviation was observed at the height of 16 m, followed by 2 m, which is at the base of the forest, and the values with least variation were at 33 m, which is above the forest canopy.…”
Section: Hourly Variation Of Reflectancementioning
confidence: 63%
“…Table I shows the basic statistics of the daily data, including the maximum and minimum values found at each height. These variations during the day refer exclusively to the relationship between reflection and solar declination, as reported by Leitão et al (2002). The highest standard deviation was observed at the height of 16 m, followed by 2 m, which is at the base of the forest, and the values with least variation were at 33 m, which is above the forest canopy.…”
Section: Hourly Variation Of Reflectancementioning
confidence: 63%
“…Apesar de apresentar um dossel arbóreo fechado, a existência de umidade nas folhas das árvores presentes nesse posto de coleta contribui para o aumento da absorção de radiação pela superfície foliar durante o dia (LEITÃO et al, 2002). Outro fator que pode explicar tais valores é a densidade da vegetação que implica na obstrução do vento, impedindo a dissipação do calor, contribuindo para o registro de temperaturas mais altas.…”
Section: Resultados E Discussõesunclassified
“…Table 1 shows the mean monthly values of r, t top‐15m , t top‐0m , FAPAR top‐15m and FAPAR top‐0m . The values of r vary from 0.027 to 0.033 with a mean value of 0.030, similar to the results obtained by Leitão et al [2002], who found 0.020 for a tropical rain forest in Manaus. The t top‐0m values range from 0.032 to 0.085, with a mean value of 0.057, and are consistent with the values obtained by Anhuf and Rollenbeck [2001], 0.045 for PAR, and by Januário et al [1992], 0.047 for global solar radiation.…”
Section: Resultsmentioning
confidence: 99%